2001
DOI: 10.1161/hc3501.093816
|View full text |Cite
|
Sign up to set email alerts
|

Right Atrial Septal Electrode for Reducing the Atrial Defibrillation Threshold

Abstract: Background-The atrial defibrillation threshold (ADFT) energy of the standard lead configuration, right atrial appendage (RAA) to coronary sinus (CS), was reduced by Ͼ50% with the addition of a third electrode traversing the atrial septum in a previous study. This study determined whether the ADFT would be lowered by a more clinically practical third electrode placed in the right atrium along the atrial septum (RSP). Methods and Results-Sustained atrial fibrillation was induced in 8 closed-chest sheep with burs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The collected data fall into 4 different categories based on the mode in which they were reported in the literature for each of the 3 parameters (ie, PR, HR, and BM): (1) measurements from single animals, (2) multiple animal measurements reported as mean values without SD, (3) multiple animal measurements reported as means with SDs, and (4) values reported as ranges without means or SDs. For convenience, the allometric equation YϭY 0 · BM b can be transformed into a logarithmic form, lnYϭlnY 0 ϩb · lnBM, which describes a straight line of the form yϭinterceptϩbx.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The collected data fall into 4 different categories based on the mode in which they were reported in the literature for each of the 3 parameters (ie, PR, HR, and BM): (1) measurements from single animals, (2) multiple animal measurements reported as mean values without SD, (3) multiple animal measurements reported as means with SDs, and (4) values reported as ranges without means or SDs. For convenience, the allometric equation YϭY 0 · BM b can be transformed into a logarithmic form, lnYϭlnY 0 ϩb · lnBM, which describes a straight line of the form yϭinterceptϩbx.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…As in ventricular defibrillation, biphasic shocks are standard, but tolerability still requires improvement. Further reductions in the atrial defibrillation threshold could be achieved by improving lead configuration 22,24,25,47–49 . One possibility that has already been tested in clinical practice is implantation of a dedicated lead in the coronary sinus (Fig.…”
Section: The Issue Of Shock‐induced Discomfortmentioning
confidence: 99%
“…One proposed strategy contemplates sequential shocks delivered through a dual‐current pathway: this approach has generated promising experimental results both in animals 50 and humans 47 . A further possibility, which so far has been tested only in animals, involves deployment of an additional shock lead at the interatrial septum 48,49 …”
Section: The Issue Of Shock‐induced Discomfortmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies have confirmed the value of the SP electrode in lowering ADFTs substantially. 25,26 Sequential shocks where the first phases of each shock were delivered at a constant level (rather than unequal shocks from a single capacitor) lowered peak voltage and current even more. 26 Studies in human patients have confirmed that additional shocking electrodes and sequential defibrillation pulses lower ADFTs.…”
Section: Alternate Electrode Locations and Sequential Shocksmentioning
confidence: 99%